Importance of continuing education for piauiense non-semi-nursing nursing professionals (Research, Society and Development, 2020)
The study aimed to know the importance of continuing education in the perception of nurses from Justin Regional Hospital Light; Identify the perceptions of nurses about the importance of Continuing Education; Ascertain the participation of nurses in the development of Continuing Education at the institution; and Relating to Continuing Education as a possible professional improvement. Held at the Regional Justino Luz Hospital in the city of Picos /PI. The study volunteers were constituted by 25 professionals, all nurses from different care units. Data were collected through semi-structured interviews with objective questions to identify and open-ended questions where the respondent had the freedom to speak, write and express their perceptions. Data were tabulated in Microsoft Excel 2010 charts analyzed and presented in the form of pizzas for better representation and comparison of results. The study revealed the importance of continuing education for the nursing staff in a hospital organization for the improvement and development of professional skills.